Frog on a log: phonics first reading fun - Harker, Jillian; Smith, Jan (Autumn Pub. Chichester, 2010)
In this whimsical tale, a frog sits on a log and observes the world around him. The story is filled with clever rhymes and humorous situations as the frog interacts with other animals, all while exploring the themes of friendship and belonging. It$1 (Bs a delightful way for kids to enjoy reading and learn about nature.s